A multilevel modular DC-DC converter topology - Vidal, Ricardo; Soto Sanchez, Diego Enrique; Andrade Aguero, Ivan Eric; Riedemann, Javier; Pesce, Cristian; Belenguer, Enrique; Pena, Ruben; Blasco-Gimenez, Ramon (My University, 2017)
A multilevel modular DC-DC power conversion topology based on cascaded H-Bridge converters in a double II configuration is presented. The topology is intended to interconnect large power DC networks. A two level control hierarchy is used to regulate the DC voltage of each H-bridge module. At the top level, DC and circulating AC currents are used to control the total energy converter in all branches (both parallels and series) of each II arrange. At bottom level, the voltage balance of a converter branch, which comprises N H-bridge modules, is carried out by balancing (N-1) capacitor voltage deviations, with respect to the average capacitor voltage. The entire topology and control strategies are simulated in a PSIM environment. Simulation results with three H-bridge converters per branch are shown and preliminary experimental results with a low power prototype are also included. (C) 2015 International Association for Mathematics and Computers in Simulation (IMACS). Published by Elsevier B.V. All rights reserved.
Keywords: dc-dc converter; multilevel modular converter; hvdc applications